Particulate and gas sampling of prescribed fires in South Georgia, USA - Sivaraman* Balachandran; Jorge E. Pachon; Sangil Lee; Michelle M. Oakes; Neeraj Rastogi; Wenyan Shi; Efthimios Tagaris; Bo Yan; Aika Davis; Xiaolu Zhang; Rodney J. Weber; James A. Mulholland; et al. (Atmospheric Environment, 2013)
Gaseous and particulate species from two prescribed fires were sampled in-situ, to better characterize prescribed burn emissions. Measurements included gaseous and fine particulate matter (PM2.5) species, particle number concentration, particulate organic carbon (POC) speciation, water-soluble organic carbon (WSOC) and water-soluble iron. Major PM2.5 components included OC (∼57%), EC (∼10%), chloride (∼1.6%), potassium (∼0.7%) and nitrate (∼0.9%). Major gaseous species include carbon dioxide, carbon monoxide, methane, ethane, methanol and ethylene. Particulate organic tracers of biomass burning, such as levoglucosan, dehydroabietic acid and retene, increased significantly during the burns. Water-soluble organic carbon (WSOC) also increased significantly during the fire and levels are highly correlated with total potassium (K) (R2 = 0.93) and levoglucosan (R2 = 0.98). The average WSOC/OC ratio was 0.51 ± 0.03 and did not change significantly from background levels. Thus, the WSOC/OC ratio may not be a good indicator of secondary organic aerosol (SOA) in regions that are expected to be impacted by biomass burning. Results using a biomass burning source profile derived from this work further indicate that source apportionment is sensitive to levels of potassium in biomass burning source profiles. This underscores the importance of quantifying local biomass burning source profiles.
Keywords: source apportionment